Git Recipes A Problem-Solution Approach - Gajda, Wlodzimierz (Apress : Imprint: Apress, 2013)
Whether you're relatively new to git or you need a refresher, or if you just need a quick, handy reference for common tasks in git, Git Recipes is just the reference book you need. With recipes to cover any task you can think of, including working with GitHub and git on BitBucket, Git Recipes shows you how to work with large repositories, new repositories, forks, clones, conflicts, differences, and it even gives you practical scenarios you may find yourself dealing with while using git. If you work with Git at all, you need this hands-on, practical reference for all things Git.